COMPREHENSIVE RESEARCH OF STRENGTH, VITALITY AND FRACTURE MECHANISMS OF REINFORCING AND COMPOSITE MATERIALS UNDER COMPLEX THERMO-MECHANICAL EFFECTS - Wildemann, V.E.; Lobanov, D.S.; Spaskova, E.M.; Babushkin, A.V.; Bikkulova, A.V.; Ilinih, A.V.; Slovikov, S.V.; Staroverov, O.A.; Temerova, M.S.; Tretyakov, M.P.; Tretyakova, T.V. (Perm Federal Research Centre Journal, 2017)
The article presents the results of RFBR grant № 13-08-96016, the purpose of which was to obtain new data about the regularities of mechanical behavior of reinforcing and composite materials under complex unsteady and combined quasi-static, dynamic, cyclic and shock effects in a wide range of temperatures to establish a scientific basis for solving strength and vitality problems of materials, risk assessment and prevention of emergency situations associated with the accumulation of structural damage and the formation of destruction conditions of the elements of important composite constructions.In this work the development of experimental research methods of the properties of reinforcing and composite materials, structural elements under complex thermomechanical effects, using advanced tests and measurement systems, as well as diagnostic tools, is carried out. Investigations have been performed concerning the viscoelastic properties of filled polymer composite materials under dynamic biharmonic and bimodal loadings with variation in the frequency of impact and temperature. New data on the patterns of accumulation of damage and destruction of carbon composite materials, depending on the types of loading on the basis of registration and processing of acoustic emission signals. Investigations have also been carried out concerning the regularities of destruction processes of semi-natural coarse-cellular samples of composite materials with a box- shaped, cellular and cellular filler, the impact of operational damage on the residual strength properties of semi-natural samples with a defect in the form of a through breakdown. New results, of research of the damaged areas of products and structural elements made of composite materials, as well as the effectiveness of reducing technological operations, have been obtained.Recommendations have been made on improving the methods of testing, control, structure and technological modes of creating composite materials and products from them in order to implement the required deformation and strength properties.